2021
DOI: 10.3390/v13102021
|View full text |Cite
|
Sign up to set email alerts
|

Spike Proteins of SARS-CoV-2 Induce Pathological Changes in Molecular Delivery and Metabolic Function in the Brain Endothelial Cells

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which causes the coronavirus disease (COVID-19), is currently infecting millions of people worldwide and is causing drastic changes in people’s lives. Recent studies have shown that neurological symptoms are a major issue for people infected with SARS-CoV-2. However, the mechanism through which the pathological effects emerge is still unclear. Brain endothelial cells (ECs), one of the components of the blood–brain barrier, are a major hurdle for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 55 publications
2
36
0
Order By: Relevance
“…SARS-CoV-2-neurovascular unit interactions were directly implicated and corroborate Krasseman and colleagues’ findings—on both a gene and a pathway level. Another earlier study demonstrated SARS-CoV-2 tropism for brain microvascular endothelial cells and the induction of microglial inflammation ( Zhang et al., 2021 ), indicated that the virus can cross the BBB via inducing disruption of the cellular basal membrane, a finding compatible with preceding research on SARS-CoV-2-BBB interactions ( Kim et al., 2021a ). Yang and colleagues have indicated that brain endothelial cells as infected by SARS-CoV-2 upregulate IFN-I signaling with interferon-induced transmembrane protein 2 (IFITM2) among specific ISGs included ( Yang et al., 2021 ), once more predicting Krasseman et al.’s findings.…”
Section: Main Textsupporting
confidence: 74%
See 1 more Smart Citation
“…SARS-CoV-2-neurovascular unit interactions were directly implicated and corroborate Krasseman and colleagues’ findings—on both a gene and a pathway level. Another earlier study demonstrated SARS-CoV-2 tropism for brain microvascular endothelial cells and the induction of microglial inflammation ( Zhang et al., 2021 ), indicated that the virus can cross the BBB via inducing disruption of the cellular basal membrane, a finding compatible with preceding research on SARS-CoV-2-BBB interactions ( Kim et al., 2021a ). Yang and colleagues have indicated that brain endothelial cells as infected by SARS-CoV-2 upregulate IFN-I signaling with interferon-induced transmembrane protein 2 (IFITM2) among specific ISGs included ( Yang et al., 2021 ), once more predicting Krasseman et al.’s findings.…”
Section: Main Textsupporting
confidence: 74%
“…We feel that the recognition of these omitted and preceding works will provide greater context to the authors ( Krasemann et al., 2022 ) and provide realistic context for the concept’s further development. The inclusion of the works presented herein ( Constant et al., 2021 ; Kim et al., 2021a , 2021b ; Lee et al., 2021 Paniz-Mondolfi et al., 2020 ; Wenzel et al., 2021 ; Yang et al., 2021 ; Zhang et al., 2021 ; Zhou et al., 2021 ) already indicates that while the authors provide a novel model of SARS-CoV-2-neurovascular unit interaction, the majority of their findings had already been predicted by preceding models, and additional strengths and caveats on its utilization apply—as indicated by clinical and in vitro studies.…”
Section: Main Textmentioning
confidence: 82%
“…In relation to this, the deposition of S1 protein has been documented in the cutaneous microvascular endothelium (41). In line with the above findings, it has also been shown that SARS-CoV-2-derived S1 protein, but not other structural proteins of the virus, can bind endothelial cells, inducing alterations in endothelial cell phenotype by enhancing the expression of cytokines, adhesive molecules and reactive oxygen species, as well as impairing cell permeability and metabolic functions (42)(43)(44)(45)(46). In addition, it has been shown that S1 can directly activate the alternative pathway of complement on the cell surface by interfering with Factor H function (47).…”
Section: Introductionmentioning
confidence: 55%
“…Spike protein alone has been shown in one study to induce several damages associated with COVID-19, including damage to the lungs and arteries, inflammation of endothelial cells lining the pulmonary artery walls, together with impairment of mitochondrial function, decrease of ACE2 expression and eNOS activity, and increase of glycolysis as observed in vitro (on endothelial cells treated for 24 h with 4 μg/mL Spike) and in vivo (upon intratracheal administration of a pseudovirus expressing Spike protein to Syrian hamsters) [124] . Spike proteins (S1 and active trimer, 15 and 30 nM) have been found to induce mitochondrial damage in brain endothelial cells [125] , and spike protein epitopes have been shown to interact with human toll-like receptor 8 (TLR 8), brain targeted Vascular Cell adhesion Molecules (VCAM1) proteins, Zonula Occludens (ZO), and some glia specific proteins (i.e., NDRG2 and Apo- S100B), which can lead to neuroinflammation [126] . Moreover, 10 nM SARS-CoV-2 viral spike proteins have been shown to alter BBB functions and induce pro-inflammatory response after 24 h in primary human brain microvascular endothelial cells (hBMVECs) cultured in 2D and 3D [127] .…”
Section: Discussionmentioning
confidence: 99%